Glacial isostatic adjustment model with composite 3-D Earth rheology for Fennoscandia - Van der Wal, W. (author); Barnhoorn, A. (author); Stocchi, P. (author); Gradmann, S. (author); Wu, P. (author); Drury, M. (author); Vermeersen, L.L.A. (author) (Geophysical Journal International, 2013)
Models for glacial isostatic adjustment (GIA) can provide constraints on rheology of the mantle if past ice thickness variations are assumed to be known. The Pleistocene ice loading histories that are used to obtain such constraints are based on an a priori 1-D mantle viscosity profile that assumes a single deformation mechanism for mantle rocks. Such a simplified viscosity profile makes it hard to compare the inferred mantle rheology to inferences from seismology and laboratory experiments. It is unknown what constraints GIA observations can provide on more realistic mantle rheology with an ice history that is not based on an a priori mantle viscosity profile. This paper investigates a model for GIA with a new ice history for Fennoscandia that is constrained by palaeoclimate proxies and glacial sediments. Diffusion and dislocation creep flow law data are taken from a compilation of laboratory measurements on olivine. Upper-mantle temperature data sets down to 400 km depth are derived from surface heatflow measurements, a petrochemical model for Fennoscandia and seismic velocity anomalies. Creep parameters below 400 km are taken from an earlier study and are only varying with depth. The olivine grain size and water content (a wet state, or a dry state) are used as free parameters. The solid Earth response is computed with a global spherical 3-D finite-element model for an incompressible, self-gravitating Earth. We compare predictions to sea level data and GPS uplift rates in Fennoscandia. The objective is to see if the mantle rheology and the ice model is consistent with GIA observations. We also test if the inclusion of dislocation creep gives any improvements over predictions with diffusion creep only, and whether the laterally varying temperatures result in an improved fit compared to a widely used 1-D viscosity profile (VM2). We find that sea level data can be explained with our ice model and with information on mantle rheology from laboratory experiments, heatflow and seismology and a pure olivine rheology ...